Generation of Dc-dc Converters With Wide Conversion Range Based on the Multistate Switching Cell - Bastos, George H. de A.; Sousa, Jefferson M. de; Costa, Levy F.; Bascopé, René P. T. (Eletrônica de Potência, 2016)
This paper presents the conception of six nonisolated dc-dc converters with wide conversion range based on the multistate switching cell (WCR-MSSC). In order to achieve wide conversion range, the multiphase transformer that is part of the multistate switching cell (MSSC) aggregates coupled secondary windings with controlled rectifiers, which are then connected in series. Then, it is possible to minimize the voltage stresses across the switches, allowing the use of MOSFETs (metal oxide semiconductor field effect transistor) with reduced on-resistance RDS(on), thus implying the significant improvement of the converter efficiency. The operation principle, qualitative analysis, quantitative analysis, and design procedure are properly presented. An experimental prototype is also developed, whose ratings are: output power PO=3 kW, input voltage VIN=84 V and output voltage VO=400 V. Some important results are then discussed in order to validate the theoretical assumptions.